PP18 Implementation of electronic patient clinical records in ambulances in the UK: a national survey. Issue 1 (14th January 2019) - Williams, Victoria; LaFlamme-Williams, Yvette; McNee, Katie; Morgan, Heather; Morrison, Zoe; WW Potts, Henry; Shaw, Debbie; Siriwardena, Niro; Snook, Helen; Spaight, Rob; Porter, Alison
Abstract : Background: The roll-out of electronic Patient Clinical Records (ePCR) across UK ambulance services has been an important aspect of modernisation. Electronic Records in Ambulances (ERA) is a two-year study which aims to describe the opportunities and challenges of implementing ePCR and associated technology in emergency ambulances. Our study includes a baseline survey of progress implementing ePCR in all UK ambulance services providing a snapshot of current usage. Methods: W e carried out semi-structured telephone interviews with information managers in each ambulance service in the UK. We asked them about the systems in use, the process and current stage of implementation and explored the perceived value of using ePCR. If services did not use ePCR we asked about plans for future introduction. The interviews were transcribed and thematically analysed, by three members of the research team. Results: We completed interviews with 22 managers from 13 services. Implementation varied across the UK. Seven services were using electronic records. Four services had adopted electronic records but, at the time of interview, had reverted to paper with the intention of implementing a new ePCR. Two services still used paper but hoped to move to ePCR in the future. Those who had fully implemented ePCR reported mixed success in terms of staff compliance, and in realising the potential benefits offered by ePCR to link with primary and secondary care. Reported benefits of ePCR were largely associated with improved data management for audit and record keeping. Potential improvements to patient care were discussed, but tended to be associated with future planned developments. Implications: Implementation of ePCR has proved challenging with wide variation in use between ambulance services. Progress has been erratic, rather than linear, demonstrated by difficulties that services experienced putting ePCR into practice. There is potential for ambulance services in the earlier stages of implementation to learn from the experiences of others.